Induction of the chloramphenicol acetyltransferase gene cat-86 through the action of the ribosomal antibiotic amicetin: involvement of a Bacillus subtilis ribosomal component in cat induction. - Duvall, E J (1985)
The plasmid gene cat-86 and the cat gene resident on pC194 each encode chloramphenicol-inducible chloramphenicol acetyltransferase activity in Bacillus subtilis. Chloramphenicol induction has been proposed to result from chloramphenicol binding to ribosomes, which then permits the drug-modified ribosomes to perform events essential to induction. If this proposal were correct, B. subtilis mutants containing chloramphenicol-insensitive ribosomes should not permit chloramphenicol induction of either cat-86 or pC194 cat. However, we and others have been unable to isolate chloramphenicol-resistant ribosomal mutants of B. subtilis 168. We therefore developed a simple procedure for screening other antibiotics for the potential to induce cat-86 expression. One antibiotic, amicetin, was found to be an effective inducer of cat-86 but not of the cat gene on pC194. Amicetin and chloramphenicol each interact with the 50S ribosomal subunit, and the mechanism of cat-86 induction by both drugs may be similar. Amicetin-resistant mutants of B. subtilis were readily isolated, and in none of six mutants tested was cat-86 detectably inducible by amicetin, although the chloramphenicol-inducible phenotype was retained. The ami-1 mutation which is present in one of these amicetin-resistant mutants was mapped by PBS1 transduction to the "ribosomal gene cluster" adjacent to cysA. Additionally, ribosomes from cells harboring the ami-1 mutation contained an altered BL12a protein, as detected in two-dimensional polyacrylamide gel electrophoresis. Lastly, an in vitro protein-synthesizing system that uses ribosomes from an ami-1-containing cell line was more resistant to amicetin than a system that uses ribosomes from an amicetin-sensitive but otherwise isogenic strain. These results indicate that the host mutation, ami-1, which effectively abolished the inducibility of cat-86 by amicetin, altered a ribosomal component.